ATP signaling is deficient in cultured Pannexin1-null mouse astrocytes - Suadicani, Sylvia O. (2012)
Pannexins (Panx1, 2 and 3) comprise a group of proteins expressed in vertebrates that share weak yet significant sequence homology with the invertebrate gap junction proteins, the innexins. In contrast to the other vertebrate gap junction protein family (connexin), pannexins do not form intercellular channels, but at least Panx1 forms non-junctional plasma membrane channels. Panx1 is ubiquitously expressed and has been shown to form large conductance (500pS) channels that are voltage-dependent, mechanosensitive and permeable to relatively large molecules, such as ATP. Pharmacological and knockdown approaches have indicated that Panx1 is the molecular substrate for the so-called “hemichannel” originally attributed to connexin43 (Cx43) and that Panx1 is the pore forming unit of the P2X(7) receptor. Here, we describe, for the first time, conductance and permeability properties of Panx1-null astrocytes. The electrophysiological and fluorescence imaging analysis performed on these cells fully support our previous pharmacological and Panx1 knockdown studies that showed profoundly lower dye uptake and ATP release than wild-type untreated astrocytes. As a consequence of decreased ATP paracrine signaling, intercellular calcium wave spread is altered in Panx1-null astrocytes. Moreover, we found that in astrocytes as in Panx1 expressing oocytes, elevated extracellular K(+) activates Panx1 channels independently of membrane potential. Thus, based on the present findings and our previous report, we propose that Panx1 channels serve as K(+) sensors for changes in the extracellular milieu such as those occurring under pathological conditions.